2013
DOI: 10.1136/bmjopen-2013-004047
|View full text |Cite
|
Sign up to set email alerts
|

Fear of childbirth predicts postpartum depression: a population-based analysis of 511 422 singleton births in Finland

Abstract: ObjectivesTo study how reproductive risks and perinatal outcomes are associated with postpartum depression treated in specialised healthcare defined according to the International Classification of Diseases (ICD)-10 codes, separately among women with and without a history of depression.DesignA retrospective population-based case–control study.SettingData gathered from three national health registers for the years 2002−2010.ParticipantsAll singleton births (n=511 422) in Finland.Primary outcome measuresPrevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
143
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(172 citation statements)
references
References 20 publications
15
143
1
9
Order By: Relevance
“…Our results are in line with those of previous studies in showing that previous mental illness is a major risk factor for PND 3,[19][20][21] . The reason for the higher prevalence of previous psychiatric illness among the controls might be that individuals with a history of severe psychiatric disease tend not to seek infertility treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with those of previous studies in showing that previous mental illness is a major risk factor for PND 3,[19][20][21] . The reason for the higher prevalence of previous psychiatric illness among the controls might be that individuals with a history of severe psychiatric disease tend not to seek infertility treatment.…”
Section: Discussionsupporting
confidence: 93%
“…However, studies have shown that the prevalence of PND cases that require psychiatric care is 0.3% 3 and that the prevalence of hospitalizations due to PND is 0.06%-0.26% 4 . Apart from the negative effects on the woman's health, PND can also have a negative impact on mother-child interaction and child development [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Significant risk factors in developed countries are antenatal depression (Leung et al, 2005;Kitamura et al, 2006;Rich-Edwards et al, 2006;Lee et al, 2007;Bilszta et al, 2008;Leigh and Milgrom, 2008;Davey et al, 2011;EscribaAguir and Artazcoz, 2011;Hamdan and Tamim, 2011;Lanes et al, 2011;Gaillard et al, 2014), antenatal anxiety (Lee et al, 2007;McGrath et al, 2008), previous psychiatric illness (Bloch et al, 2005;Chee et al, 2005;Eilat-Tsanani et al, 2006;Mosack and Shore, 2006;Rich-Edwards et al, 2006;Baker and Oswalt, 2008;Bilszta et al, 2008;Leigh and Milgrom, 2008;Davey et al, 2011;Abbasi et al, 2013;Raisanen et al, 2013), poor martial relationship (Escriba-Aguir and Artazcoz, 2011), stressful life events (Boyce and Hickey, 2005;Rubertsson et al, 2005;Escriba-Aguir and Artazcoz, 2011), child care stress (Leung et al, 2005) and negative attitude towards pregnancy (Kitamura et al, 2006). The psychological factors for postpartum depression documented only in developed countries are poor mental health (Sword et al, 2011), poor quality of life (de Tychey et al, 2008), history of premenstrual dysphoric disorders (Bloch et al, 2005), intention of returning to work (Kozinszky et al, 2011) and perceived stress (Wang and Chen, 2006).…”
Section: Psychological Factorsmentioning
confidence: 98%
“…Recently Raisanen et al [17] explored perinatal risks for developing postnatal depression in more than 500,000 Finnish women. Although a history of depression was highly related to postnatal depression, these authors also reported that women with childbirth fear and no history of depression were almost three times more likely to develop postnatal depression [17].…”
Section: Introductionmentioning
confidence: 99%